The Use of Digital Storytelling in Improving Students’ Speaking Skills at Mts Madani Alauddin Pao-Pao - Nurhasna Basri; Muhammad Tahir; Maemuna Muhayyang (International Journal of Language, Education, and Literature, 2026)
This research used quantitative approach with quasi experimental design. The population of the research was the eighth-grade students. The sample was 20 students as experimental class and 20 students as control class. The researcher used speaking test, and students’ questionnaire as the instruments of this research. This research analyzed the effect of the use digital storytelling in improving students’ speaking skills. The aims of the research were to find out (1) the effect of digital storytelling on students’ speaking skills at MTs Madani Alauddin Pao-Pao, (2) the students’ perception of the use digital storytelling on students’ speaking skills at MTs Madani Alauddin Pao-Pao.The design of this research was quantitative research through quasi experimental using non-equivalent group design. Quasi experimental in this research will be used to measure the effect of the objects being experimented. It also aims to compare two groups, experimental and control group which were given different treatments through the media usage. The result showed that the mean score of pre-tests in experimental class was 51.8 and in control class was 52.4. and the mean score of experimental class in post-posttest was 66.5 and control class was 58.61. There was significant effect of the mean score between two groups on students’ speaking skills in using digital storytelling and not in MTs Madani Alauddin Pao-pao. The study concluded that the use of digital storytelling has a positive impact on students' speaking skills at MTs Madani Alauddin Pao- pao. Students feel more confident, more creative, and can better organize their ideas. Despite challenges in terms of technical skills and the time required to create digital stories, the benefits gained from using digital storytelling are significant in improving students' speaking skills.